Report of a rare case of ovarian ectopic pregnancy following ipsilateral salpingectomy and review of literature - Thomas, Anuja; Thompson, Aisling; Mcilwaine, Patrick (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This is the case report of an ovarian ectopic pregnancy in a lady who had undergone ipsilateral salpingectomy previously. A 35-year-old lady, P1+1, was admitted with lower abdominal pain at 6 weeks of gestation. She had a caesarean section in her first pregnancy followed by a left sided tubal ectopic pregnancy managed by laparoscopic left salpingectomy. Transvaginal scan showed a mass in the left adnexa. Laparoscopy revealed a suspected ovarian ectopic pregnancy which was removed. The diagnosis was confirmed by histopathological examination. Ectopic pregnancy occurs in 1-2% of all pregnancies and is an important cause of maternal morbidity and mortality. Recurrence of ectopic pregnancies are rare, ranging from 6-28%. Ovarian ectopic pregnancy following ipsilateral salpingectomy is a rare occurrence. Timely diagnosis and management are vital for preventing morbidity and mortality.